What can patients tell us about the quality and safety of hospital care? Findings from a UK multicentre survey study. Issue 9 (15th March 2018) - O'Hara, Jane K; Reynolds, Caroline; Moore, Sally; Armitage, Gerry; Sheard, Laura; Marsh, Claire; Watt, Ian; Wright, John; Lawton, Rebecca
Abstract : Background: Patient safety measurement remains a global challenge. Patients are an important but neglected source of learning; however, little is known about what patients can add to our understanding of safety. We sought to understand the incidence and nature of patient-reported safety concerns in hospital. Methods: Feedback about the experience of safety within hospital was gathered from 2471 inpatients as part of a multicentre, waitlist cluster randomised controlled trial of an intervention, undertaken within 33 wards across three English NHS Trusts, between May 2013 and September 2014. Patient volunteers, supported by researchers, developed a classification framework of patient-reported safety concerns from a random sample of 231 reports. All reports were then classified using the patient-developed categories. Following this, all patient-reported safety concerns underwent a two-stage clinical review process for identification of patient safety incidents. Results: Of the 2471 inpatients recruited, 579 provided 1155 patient-reported incident reports. 14 categories were developed for classification of reports, with communication the most frequently occurring (22%), followed by staffing issues (13%) and problems with the care environment (12%). 406 of the total 1155 patient incident reports (35%) were classified by clinicians as a patient safety incident according to the standard definition. 1 in 10 patients (264 patients) identified a patient safety incident, with medication errors the most frequently reported incident. Conclusions: Our findings suggest that patients can provide insight about safety that complements existing patient safety measurement, with a frequency of reported patient safety incidents that is similar to those obtained via case note review. However, patients provide a unique perspective about hospital safety which differs from and adds to current definitions of patient safety incidents. Trial registration number: ISRCTN07689702 ; pre-results.